(untitled) (Transport systems and technologies, 2018)
The conceptual regulations of the construction and organization of a railway line on the section of the ports of Odessa – the border with the EU, as part of the New Silk Route by the territory of Ukraine are considered. Implementation of these conceptual provisions is construction and successful commercial operation of high-speed railway 1435 mm track gauge.